Meningococcal carriage in Dutch adolescents and young adults; a cross-sectional and longitudinal cohort study. (August 2017) - van Ravenhorst, M.B.; Bijlsma, M.W.; van Houten, M.A.; Struben, V.M.D.; Anderson, A.S.; Eiden, J.; Hao, L.; Jansen, K.U.; Jones, H.; Kitchin, N.; Pedneault, L.; Sanders, E.A.M.; et al.
Abstract: Objectives: Current information on rates and dynamics of meningococcal carriage is essential for public health policy. This study aimed to determine meningococcal carriage prevalence, its risk factors and duration in the Netherlands, where meningococcal C vaccine coverage is >90%. Several methods to identify serogroups of meningococcal carriage isolates among adolescent and young adults were compared. Methods: Oropharyngeal swabs were collected from 1715 participants 13–23 years of age in 2013–2014; 300 were prospectively followed over 8 months. Cultured isolates were characterized by Ouchterlony, real-time (rt-) PCR or whole-genome sequencing (WGS). Direct swabs were assessed by rt-PCR. Questionnaires on environmental factors and behaviour were also obtained. Results: A meningococcal isolate was identified in 270/1715 (16%) participants by culture. Of MenB isolates identified by whole genome sequencing, 37/72 (51%) were correctly serogrouped by Ouchterlony, 46/51 (90%) by rt-PCR of cultured isolates, and 39/51 (76%) by rt-PCR directly on swabs. A sharp increase in carriage was observed before the age of 15 years. The age-related association disappeared after correction for smoking, level of education, frequent attendance to crowded social venues, kissing in the previous week and alcohol consumption. Three participants carried the same strain identified at three consecutive visits in an 8-month period. In these isolates, progressively acquired mutations were observed. Conclusions: Whole genome sequencing of culture isolates was the most sensitive method for serogroup identification. Based upon results of this study and risk of meningococcal disease, an adolescent meningococcal vaccination might include children before the age of 15 years to confer individual protection and potentially to establish herd protection.